Plaque Structural Stress Estimations Improve Prediction of Future Major Adverse Cardiovascular Events After Intracoronary Imaging. (June 2016) - Brown, Adam J.; Teng, Zhongzhao; Calvert, Patrick A.; Rajani, Nikil K.; Hennessy, Orla; Nerlekar, Nitesh; Obaid, Daniel R.; Costopoulos, Charis; Huang, Yuan; Hoole, Stephen P.; Goddard, Martin; West, Nick E.J.; et al.
Abstract : Background—: Although plaque rupture is responsible for most myocardial infarctions, few high-risk plaques identified by intracoronary imaging actually result in future major adverse cardiovascular events (MACE). Nonimaging markers of individual plaque behavior are therefore required. Rupture occurs when plaque structural stress (PSS) exceeds material strength. We therefore assessed whether PSS could predict future MACE in high-risk nonculprit lesions identified on virtual-histology intravascular ultrasound. Methods and Results—: Baseline nonculprit lesion features associated with MACE during long-term follow-up (median: 1115 days) were determined in 170 patients undergoing 3-vessel virtual-histology intravascular ultrasound. MACE was associated with plaque burden ≥70% (hazard ratio: 8.6; 95% confidence interval, 2.5–30.6; P <0.001) and minimal luminal area ⩽4 mm 2 (hazard ratio: 6.6; 95% confidence interval, 2.1–20.1; P =0.036), although absolute event rates for high-risk lesions remained <10%. PSS derived from virtual-histology intravascular ultrasound was subsequently estimated in nonculprit lesions responsible for MACE (n=22) versus matched control lesions (n=22). PSS showed marked heterogeneity across and between similar lesions but was significantly increased in MACE lesions at high-risk regions, including plaque burden ≥70% (13.9±11.5 versus 10.2±4.7; P <0.001) and thin-cap fibroatheroma (14.0±8.9 versus 11.6±4.5; P =0.02). Furthermore, PSS improved the ability of virtual-histology intravascular ultrasound to predict MACE in plaques with plaque burden ≥70% (adjusted log-rank, P =0.003) and minimal luminal area ⩽4 mm 2 ( P =0.002). Plaques responsible for MACE had larger superficial calcium inclusions, which acted to increase PSS ( P <0.05). Conclusions—: Baseline PSS is increased in plaques responsible for MACE and improves the ability of intracoronary imaging to predict events. Biomechanical modeling may complement plaque imaging for risk stratification of coronary nonculprit lesions. Abstract : Supplemental Digital Content is available in the text.